Animals : can you find the odd one out? - Peto,Violet (London, Dorling Kindersley Limited, 2017)
Little learners will love Spot the Difference Animals, filled with fun facts, questions, and some hilariously out-of-place animals. Will they find the monkey wearing lipstick, or the cat with a snake for a tail? Whether comparing two pictures to find the differences, or looking for the odd one out in repeated patterns, young readers will develop observational skills, and they'll be having so much fun they won't even know they're learning! With amazing facts and questions on every page, Spot the Difference Animals is the perfect activity book for little ones aged 2 to 5 to learn about animals and have fun doing it
Keywords: Spot the difference book